KAJIAN BEBERAPA KARAKTERISTIK TANAH GAMBUT PADA LAHAN TERBAKAR DAN TIDAK TERBAKAR DI PERKEBUNAN KELAPA SAWIT - Virmanto, Dedy; Sa'ad, Asmadi; Arsyad, AR; Ermadani, Ermadani (Departemen Ilmu Tanah dan Sumberdaya Lahan, Fakultas Pertanian Universitas Andalas, 2022)
The excessive drainage system on peat causes the peat to dry out, especially during the dry season. This condition triggers the occurrence of extensive and intensive land fires, which causes changes in the characteristics of peat soils. This study aimed to study the characteristics of peat soil consisting of several physical and chemical properties of peat on burned and unburned land in oil palm plantations in Pematang Raman Village, Kumpeh District, Muaro Jambi Regency. The research was carried out using a survey method. Observation block area was determined by purposive sampling based on adjacent land conditions (burned and unburned). Observation points were set on a grid that was perpendicular to the canal with a horizontal distance of 200 m from 1000 m block length and a vertical distance of 50 m from 300 m block width with an area of each block + 30 ha. The time interval between the fire incident and sampling was 17 months. Soil samples were taken at a depth of 0-20 cm and 20-40 cm. The results showed that the physical and chemical properties of burnt and unburned peat showed differences in the level of maturity, physical and chemical properties of the soil. Burnt peat soil had a faster weathering rate as indicated by the dominance of the sapric maturity level in the top layer (0-20 cm) and below the surface (20-40 cm). The bulk density, ash content, and pH of the burned peat soil were higher, while the C-organic content, total N, C/N, and water content were lower.Keywords: burned; chemical and physical properties; peat soils